Urgensi Memahami Arbitrase Bagi Pemangku Kepentingan Dunia Bisnis Di Indonesia - Hariyanto, Bambang; Saptarini, Saptarini (Jurnal Hukum & Pembangunan, 2024)
Abstract The resolution of business disputes through arbitration forums is increasingly favored by the majority of business actors in Indonesia. One indication of this is the growing number of business actors, both from the private sector and state-owned enterprises, who include arbitration agreements as dispute clauses in their contracts. Arbitration has even attracted the interest of MSMEs (Micro, Small, and Medium Enterprises) as a forum to resolve their business disputes. This phenomenon ultimately highlighted the urgency for stakeholders in the business world to understand arbitration. Using normative juridical methods, this article contained a series of analyses of primary materials, including legislation and other relevant studies, to demonstrate the increased interest of the business community in choosing arbitration as a dispute resolution forum. This growing interest underscored the necessity for business stakeholders to have a proper understanding of arbitration. The analysis revealed that the trend of increasing interest in arbitration was not aligned with the understanding of business stakeholders regarding the forum, both conceptually and in practice. This situation can hinder them in formulating good arbitration agreement dispute clauses. Therefore, it was necessary to develop training and education curricula on arbitration for business stakeholders to gain a comprehensive understanding of arbitration. Keywords: Alternative Dispute Resolution in Business, State-Owned Enterprises, Beneficial Settlements